Political consequences of consumer debt relief - Toke Aidt; Zareh Asatryan; Lusine Badalyan (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2022)
We study consumer debt relief as a tool of distributive politics and ask if debt relief can influence elections. We utilize quasi-experimental variation generated by a very large debt relief program enacted in the Republic of Georgia by a private foundation that affected every sixth voter. We estimate that the program helped the incumbent candidate linked to the foundation win the 2018 Presidential election, and that its effects persisted into the next election. We show how economic power can translate into political power in polities with de jure competitive elections but with de facto weak accountability.
Keywords: D72; E51; O10; 330; Consumer debt relief; distributive politics; vote buying; elections